Synthesis and biological assessment of novel acylhydrazone derivatives of 2-methyl-1,4- naphthoquinone - Elaridi, Jomana (2017)
Naphthoquinones are medicinally important molecules with a diverse array of biological properties such as antimicrobial, antifungal, antiviral, anti-inflammatory, anti-artherosclerotic and anticarcinogenic activities. In this study, we report the simple and direct preparation of a new group of novel menadione-hydrazone conjugates by reaction of 2-methyl-1,4-naphthoquinones with several aliphatic, aromatic and nucleobase hydrazides. The menadione-hydrazone conjugates were produced in excellent yields and characterized by IR, NMR and HRMS. The menadione derivatives were tested for their anticancer effects against human colon cancer HCT116 and human breast cancer MCF-7 cell lines. Interestingly, the molecules displayed disparate activities against both cell lines; the menadione hydrazones derived from the lipophilic myristic hydrazide and stearic hydrazide exhibited the most potent activity against HCT116 cell lines with IC50 of 89 and 64 μM. The most effective compounds against MCF-7 cells were the lauric hydrazide and benzoic hydrazide-derived menadione hydrazones with IC50 of 56 µM.